2017
DOI: 10.1051/parasite/2017048
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic regulation during acute hepatic infection withEntamoeba histolyticain the hamster: involvement of oxidative stress, Nrf2 and NF-KappaB

Abstract: Oxidative stress and transcriptional pathways of nuclear factor erythroid 2-related factor 2 (Nrf2) and nuclear factor kappa-B (NF-κB) are critically involved in the etiopathology of amebic liver abscess (ALA). In this work, we studied the relationship between the adrenergic nervous system and ALA in the hamster. ALA was visible at 12 h of infection. While 6-hydroxidopamine (6-OHDA) decreased infection, propranolol (β-adrenergic blocker) treatment was associated with less extensive liver damage, and phentolami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…Previous studies have reported that Nrf2 is involved in the regulation of antioxidant responses and inflammation (21)(22)(23)(24). Western blotting demonstrated that the protein expression of Nrf2 and HO-1, which lies downstream of Nrf2, was further upregulated in osthole-treated BV2 microglia, compared with cells exposed to LPS alone (Fig.…”
Section: Effects Of Osthole On the Protein Expression Of Nrf2 And Ho-1mentioning
confidence: 71%
“…Previous studies have reported that Nrf2 is involved in the regulation of antioxidant responses and inflammation (21)(22)(23)(24). Western blotting demonstrated that the protein expression of Nrf2 and HO-1, which lies downstream of Nrf2, was further upregulated in osthole-treated BV2 microglia, compared with cells exposed to LPS alone (Fig.…”
Section: Effects Of Osthole On the Protein Expression Of Nrf2 And Ho-1mentioning
confidence: 71%
“…Oxidative stress is critically involved in the etiopathology of ALA [29]. There has been evidence that CUR exerts a hepatoprotective effect against oxidative stress via up-regulation of antioxidant enzyme genes [30,31].…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, the overproduced ROS is scavenged via the activation of Nrf2 [ 70 ]. The inactivation of Nrf2 signaling is reported to be beneficial for the overactivation of NF- κ B [ 71 ].…”
Section: Discussionmentioning
confidence: 99%